2018
DOI: 10.4067/s0717-95022018000300909
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Analysis of Testis of the Guinea Fowl ( Numida meleagris ) Under Tropical Savannah Climate of India

Abstract: The present study aimed to document the seasonal variations in the testicular morphology of the adult guinea fowl (Numida meleagris) under tropical savannah climate of India. The study was conducted in 24 adult healthy guinea cocks. The testes were ovoid in shape throughout the year. The consistency of the testes was moderately firm with great resilience and creamy white in colour during summer and monsoon-I whereas soft in consistency and dull white to yellowish tinge in colour during monsoon-II and winter se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…As shown in the Table 1, the GSI of 8, 16, and 24 turkeys were 0.96 ± 0.32%, 1.32 ± 0.42%, and 9.53 ± 8.26%, respectively. According to Dharani et al [17], the GSI relates to the efficiency of spermatozoa production in males. In this study, it was found that the GSI of the 24-week old turkeys largely increased compared to the previous age groups, RT LT reflecting that at the age of 24 weeks, sperm reproduction in turkeys was already very efficient.…”
Section: Gonadosomatic Indexmentioning
confidence: 99%
“…As shown in the Table 1, the GSI of 8, 16, and 24 turkeys were 0.96 ± 0.32%, 1.32 ± 0.42%, and 9.53 ± 8.26%, respectively. According to Dharani et al [17], the GSI relates to the efficiency of spermatozoa production in males. In this study, it was found that the GSI of the 24-week old turkeys largely increased compared to the previous age groups, RT LT reflecting that at the age of 24 weeks, sperm reproduction in turkeys was already very efficient.…”
Section: Gonadosomatic Indexmentioning
confidence: 99%
“…Additionally, the bird is used for different cultural purposes, and plays a role in poverty reduction among rural dwellers [ 11 ]. The bird also breeds seasonally and reaches its peak breeding activity during the summer period [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bright yellow in juveniles and grey-white in adults of the quails and ostrich. The bright yellow colour in juveniles is due to the accumulation of lipids in the interstitial cells and the grey-white colour in adults due to the spread of interstitial cells by enlarging seminiferous tubules after sexual maturity [20]. The results of this study, most of the testicle's colour in DOC Arab chickens is yellow-white (creamy), the findings of the other colours besides bright yellow, still have to be confirmed histologically to support the determination of its quality.…”
Section: Morphometric and Gross Anatomy Of Day-old Arabic Chick Testesmentioning
confidence: 99%